Influence of Post-Mortem Ageing Prior to Processing on the Carcass Quality of Japanese Quail - Vijay, Loganathan; Muthusamy ,; Karthikeyan, Natesan; Pandiyan, Chinnusamy (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
An investigation was carried out to assess the impacts of different ageing periods on various quality attributes of Japanese quail meat. Six-week old 72 birds (36 males and 36 females) were slaughtered after starving for 4 h. Following the dressing operations, the whole carcasses were subjected to the ageing process at 3±1°C for 2½ h. During the ageing process, continuous measurements of pH, water-holding capacity (WHC), shear-force value (SFV) and sensory evaluation of the breast muscles from the carcasses was done  at an interval of 30 min. The ultimate pH value of 5.5 – 5.7 was reached in the meat samples within the first h of ageing process. The water-holding capacity (WHC) started to decrease and obtained a minimum percent by the end of first h. Subsequently, the WHC was enhanced at the ageing period of 2½ h. The shear force values were high at 1 h of ageing and were low at 2½ h. The scores of the sensory evaluation revealed that the meat samples that were aged for 2 and 2½ h were superior in terms of flavour, juiciness, tenderness and overall acceptability, when compared to the lesser time aged and unaged meat samples. From the above results, it can be concluded that a minimum ageing period of 2 to 2 ½ h is appropriate to bring about the desirable quality attributes in the Japanese quail meat.
Keywords: Ageing; Japanese quail; Shear force; Tenderness and WHC